An ethnography approach as in a way of extending nursing care - Vieira, Luiza Jane Eyre de Souza; Barroso, Maria Grasiela Teixeira (Rev Rene, 2001)
The ethnography is a method which is appropriated to find the way of living, people’s experiences, feelings, patterns, meanings, attitudes, behaviors and actions. The study’s purpose consisted of talking about an ethnography approach as a way for extending a nursing caring. An ethnographic approach was used as methodology. The description of cultural domains showed how the families had perceived poisoning cases with their children, how the families had felt and which sociocultural factors, accord to world view’s families, that are influencing in children’ safety. Understanding that ethnographic studies to provide a knowledge about the natural environment of the people and they become useful in planning and implementing the guidelines which are present at nursing caring.